2012
DOI: 10.1002/phar.1047
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Alvimopan for Prevention and Management of Postoperative Ileus

Abstract: Alvimopan was cost saving for prevention of postoperative ileus in patients undergoing bowel resection by laparotomy, although these potential cost savings were highly dependent on a difference in time to discharge order written. This finding is not applicable to the less-invasive laparoscopic surgical approach for which quality data on alvimopan use are lacking. Limitations of this analysis included use of time to discharge order written as a proxy for length of stay and difficulty interpreting study results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Several high‐quality trials have been performed to investigate its clinical effect and meta‐analyses of these data have shown that, compared with placebo, a 12 mg dose of alvimopan accelerates time to tolerance of an oral diet, time to passage of first bowel motion and time to discharge both within and outside Enhanced Recovery After Surgery (ERAS) programs . Alvimopan has been approved by the US Food and Drug Administration and is widely used in the US for these purposes …”
Section: Pathophysiological Basis Of and Risk Factors For Poimentioning
confidence: 99%
“…Several high‐quality trials have been performed to investigate its clinical effect and meta‐analyses of these data have shown that, compared with placebo, a 12 mg dose of alvimopan accelerates time to tolerance of an oral diet, time to passage of first bowel motion and time to discharge both within and outside Enhanced Recovery After Surgery (ERAS) programs . Alvimopan has been approved by the US Food and Drug Administration and is widely used in the US for these purposes …”
Section: Pathophysiological Basis Of and Risk Factors For Poimentioning
confidence: 99%
“…A pooled analysis of data from the phase III trials with alvimopan showed that it significantly shortened the time to return of normal gastrointestinal function by a mean of 12–15 hours (p≤0.001) and time to discharge readiness by a mean of 14–18 hours (p<0.001) . Furthermore, a pharmacoeconomic analysis demonstrated alvimopan to be a cost‐saving intervention in patients undergoing open bowel resection when the time to discharge is reduced by 3.5 hours …”
Section: Postoperative Ileusmentioning
confidence: 99%
“…(13, 14, 25–27) In our study, use of alvimopan was associated with a cost savings of $636. Due to the fact that charges (and subsequently costs) are not itemized in CHARS, the mechanism of this cost savings is not known.…”
Section: Discussionmentioning
confidence: 60%